2006
DOI: 10.1128/jvi.80.5.2349-2357.2006
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Viral Populations Differentiate and Evolve Independently in a Single Perennial Host Plant

Abstract: The complex structure of virus populations has been the object of intensive study in bacteria, animals, and plants for over a decade. While it is clear that tremendous genetic diversity is rapidly generated during viral replication, the distribution of this diversity within a single host remains an obscure area in this field of science. Among animal viruses, only Human immunodeficiency virus and Hepatitis C virus populations have recently been thoroughly investigated at an intrahost level, where they are struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 48 publications
3
77
0
1
Order By: Relevance
“…The insensitivity to s was still enhanced by increasing values of . is an important parameter to take into account for plant viruses, because compartmentalization of virus variants within plants was frequently observed (15,26,27) and may be the consequence of genetic drift that occurred at the plant tissue level during plant infection.…”
Section: Discussionmentioning
confidence: 99%
“…The insensitivity to s was still enhanced by increasing values of . is an important parameter to take into account for plant viruses, because compartmentalization of virus variants within plants was frequently observed (15,26,27) and may be the consequence of genetic drift that occurred at the plant tissue level during plant infection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that plum pox virus has evolved into several distinct populations to the point that in different parts of the same Prunus tree, the composition of these populations was different over a period of 13 years after inoculation (Jridi et al, 2006). It will be interesting to pursue similar studies with GRSPaV to better understand the dynamics of genetic Genetic diversity and putative recombination in GRSPaV diversity and the potential association between different Vitis spp.…”
Section: Recombinant Isolatementioning
confidence: 99%
“…Because of the genome compatibility of PVY strains, the No recombination in artificial potyvirus infections probability of finding recombinants of PVY/PVY is expected to be higher than detecting recombinants between PPV/TVMV, PPV-SK68/PVY-H or PVA/PVY-O. However, we can not state categorically that the time frame from inoculation to RNA isolation (up to four weeks) was sufficient to generate recombinant genomes, since Jridi et al (2006) have recently shown that sequence heterogeneity in PPV occurred in a plum tree over 13 years after a single infection. In future studies, the experimental design should critically address the period from inoculation to detection of recombinant viruses.…”
Section: Future Risk Assessment Of Vrtpsmentioning
confidence: 93%